2019
DOI: 10.3727/096504018x15235274183790
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and In Silico Analysis of Cordycepin and its Derivatives as Endometrial Cancer Treatment

Abstract: The aim of this study was to investigate the inhibition effects of cordycepin and its derivatives on endometrial cancercell growth. Cytotoxicity MTT assays, clonogenic assays and flow cytometry were used to observe the effects on apoptosis and regulation of the cell cycle of Ishikawa cells under various concentrations of cordycepin, cisplatin and combinations of the two. Validated docking simulations were performed on 31 cordycepin derivatives against adenosine deaminase (ADA) to predict their binding affiniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
1
22
0
1
Order By: Relevance
“…9 However, ADA inhibitors can cause unacceptable side effects to patients. 8 The nanoscale of Au NS means it can be safely eliminated through the urinary system, thus Au NS is a star-shaped nanomaterial with a coarse surface and high surface-to-volume ratio, which allows it to act as a drug carrier for anticancer drug delivery. 18 Au NS has shown its ability to facilitate and localize drug molecules into tumor cells by the enhanced permeation retention effect.…”
Section: Resultsmentioning
confidence: 99%
“…9 However, ADA inhibitors can cause unacceptable side effects to patients. 8 The nanoscale of Au NS means it can be safely eliminated through the urinary system, thus Au NS is a star-shaped nanomaterial with a coarse surface and high surface-to-volume ratio, which allows it to act as a drug carrier for anticancer drug delivery. 18 Au NS has shown its ability to facilitate and localize drug molecules into tumor cells by the enhanced permeation retention effect.…”
Section: Resultsmentioning
confidence: 99%
“…At a dose of 56.50 µg/mL the inhibition rate was 94.39% ± 2.27% for Ishikawa cells and 99.63% ± 0.16% for HEC-1A cells, which showed that MRS5698 is highly effective in inhibiting cell proliferation in both cell lines. According to a previous study, 12 the IC 50 value of cordycepin on Ishikawa cells was 89.03 µg/mL, which is much higher than that of MRS5698 on the same cell line. It indicated that MRS5698 had a better inhibitory effect on Ishikawa cells.…”
mentioning
confidence: 79%
“…Interestingly, all of the apoptotic rates in the cisplatin groups did not reach 10% for Ishikawa cell lines. According to Fong et al, 12 cell cycle analysis with cisplatin was conducted on Ishikawa cells, the result of which showed that cisplatin arrested the S-phase in the cell cycle and inhibited the growth of Ishikawa cells. Cisplatin-induced apoptosis is a long and complicated procedure.…”
mentioning
confidence: 99%
“…In practical research, the molecular docking score is widely used [ 46 ]. Fong P. et al used molecular docking scores to evaluate the possibility of cordycepin and its derivatives as therapeutic agents for endometrial cancer [ 28 ]. In the study of molecular docking evaluation of 31 compounds, the compound numbered MRS5698 was finally successfully screened as a candidate molecule.…”
Section: Virtual Screening Technologymentioning
confidence: 99%